Some Properties of Relative Bi-(Int-)Γ-Hyperideals in Ordered Γ-Semihypergroups - Rao, Yongsheng; Xu, Peng; Shao, Zehui; Kosari, Saeed; Omidi, Saber (Frontiers in Physics, 2020)
In this paper, we study the concept of relative bi-Γ-hyperideals (J -bi- Γ-hyperideals) in ordered Γ-semihypergroups and present some related examples of this concept. Especially, characterization of J -simple ordered Γ- semihypergroups in terms of J -bi-Γ-hyperideals is given. Furthermore, we define the notion of J -(bi-)int-Γ-hyperideals in ordered Γ-semihypergroups and investigate its related properties. We show that J -int-Γ-hyperideals and J -Γ-hyperideals coincide in a J -regular ordered Γ-semihypergroup.